The product design preferences based on Kansei engineering: car products in Malaysia - Sihombing, Haeryip; Wan Nor Azman, Wan Ainul Syafika; Sulaiman, Shamsuddin; Salleh, Mohd Rizal; Yaakob, Mohd Yuhazri (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
This study discussed the customer preferences towards the product design profiles based on Kansei Engineering. The purpose of this study is to find out what the emotional preferences (Kansei) towards the car design profile using developed questionnaires of Kansei words (Stylish, Comfortable, Safe, Sporty, and Luxury) and 6 car product design (City, Sedan, and MPV) launched in Malaysia for years 2014 - 2016. Based on the finding of the survey distributed to171 respondents in Melaka, the most customer preferences against the car design are 'Comfortable', 'Luxury' and 'Stylish'. The 'Comfortable' is as the most customer preferences towards the MPV and City car, while 'Luxury' towards Sedan car. The most significant correlation found between car product towards customers were on 'Side' and 'Rear' view of the car, while on 'Front'' view is none. The significant correlation to the side view of MPV is influenced by gender, while occupation to the City, and age to Sedan.